Procedure for forming, on a solid substrate, a film with properties similar to those of diamonds, the solid bodies so coated and the self-sustained film so obtained - Huck, Hugo Alberto; Jech, Alberto Estanislao; Righini, Raúl; Halac, Emilia Beatriz; Rodríguez de Benyacar, María Angélica; Nicolai, Julio Antonio (1993)
Fil: Huck, Hugo Alberto. Comisión Nacional de Energía Atómica; Argentina.